CASE OF SUCCESSFUL EMERGENCY ENDOVASCULAR REPAIR OF RUPTURED ABDOMINAL AORTIC ANEURYSM IN ANATOMICALLY DIFFICULT CONDITIONS - R. S. Tupikin; S. K. Chibirov; A. A. Zebelyan; A. N. Fedorchenko (Инновационная медицина Кубани)
This report presents a clinical case of emergency endovascular treatment of acute rupture of the abdominal aortic aneurysm in complex anatomically difficult conditions. Although this pathology is rare, it has a high mortality rate. Moreover, according to different authors endovascular repair is safer as compared with open surgery. We demonstrate the decision-making algorithm, show the technical nuances during the intervention which allowed us to achieve an acceptable clinical and angiographic result. Our experience will be interesting and useful for specialists who treat patients with vascular diseases.